Pluralisme dalam Pendidikan Islam: Studi Pemikiran Prof. Dr. Nurcholish Madjid - Irfan Efendi (Universitas Muhammadiyah Malang, 2018)
Pluralism is not only a theological consciousness, but also social consciousness. This has implications for the awareness that humans live in a pluralistic society in terms of religion, culture, ethnicity and various other diversity. According to Nurcholish Madjid, Islamic education, both formal and non-formal, is a bridge to internalize pluralistic values or inclusive creeds to students. Al-Quran is the main foundation of Islamic education practice. On that basis, Islamic education is required to present social morality so that the humanistic messages contained in the holy book can be used as guidelines for civilized social life. This research wants to look in more detail about Nurcholsih Madjid's framework of thinking about religious pluralism in Islamic education. This research uses the literature review method, so that the writing refers to the sources of writing, such as articles, journals, books that are in accordance with the discussion of this research.